Preface to the special issue on monitoring and modelling of carbon-balance-, water- and snow-related phenomena at northern latitudes - Aalto, Tuula; Peltoniemi, Mikko; Aurela, Mika; Böttcher, Kristin; Gao, Yao; Härkönen, Sanna; Härmä, Pekka; Kilkki, Juho; Kolari, Pasi; Laurila, Tuomas; Lehtonen, Aleksi; Manninen, Terhikki; et al.
2015